Analysis Of Marketing Communication Activities In Increasing Brand Equity Of Lion Air Airline - Yulianti Keke; Veronica Veronica; Siska Amonalisa Silalahi; Juliater Simarmata; Selma Novaliza Husna (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Lion Air is a minimal expense transporter carrier and the biggest commercial aircraft in Indonesia. The Lion Air application on the Google Play Store and AppStore gets a low rating compared to other airlines, Lion Air's social media is less well known among the public and the low number of followers on Lion Air's social media compared to other airlines' social media and many comments containing complaints and Unanswered questions on Lion Air's Instagram page have resulted in a decline in Lion Air's Top Brand Index in the airline category over the last few years, so it is necessary to carry out appropriate marketing communications for Lion Air. The marketing communications carried out by Lion Air are expected to increase the airline's brand equity, so this research was conducted to determine and investigate the impact of web-based and electronic verbal entertainment (e-WOM) promotion exercises on the brand value of the airline Lion Air. This exploration uses quantitative techniques using multiple linear regression methods with a total of 140 respondents. The consequences of investigating the impact of marketing communication activities via social media and electronic word of mouth (e-WOM) together on the brand value of Lion Air airlines show the strong relationship between marketing communications via social media, electronic word of mouth and brand equity.